An analytical beam model for the evaluation of crack tip root rotations and displacements in orthotropic specimens (Fracture and Structural Integrity, 2020)
Explicit and simple expressions for root compliance coefficients, which can be used to define root rotations and root displacements at the crack tip cross section of orthotropic cracked beams, are derived under general self-equilibrated loading conditions at the crack tip. The effects of both shear deformations and transverse elasticity are taken into account in order to accurately define displacement fields and energy release rate. The derivation builds on and extends one-dimensional formulations in the literature. The employment of the novel analytical expressions requires the determination of one a priori unknown parameter which describes the effects of the transverse elasticity and is determined through matching of well established 2D results in the literature. The one-dimensional model accurately reproduces crack tip effects in symmetric isotropic and orthotropic specimens; shear deformations are included in the formulation for an accurate derivation of the root displacement coefficients; the accuracy reduces in asymmetric specimens where the matching parameter becomes load dependent.
Keywords: Root rotations; Root displacements; Collinear delamination; Fracture specimens; Orthotropy